La “Battaglia della Colonna” tra Ottone II di Sassonia e l’Emiro Abū l-Qāsim nel 982 - Loiacono, Antonio Maurizio 1981- (2018)
The serious defeat of the German-Lombard troops led by Otto II of Saxony in July of the 982, during the battle against the Sicilian Emir Abū al-Qāsim, was the final moment of a military campaign whose aim was gaining the provinces of Southern Italy to the Holy Roman Empire. The story had a large echo in ancient sources and it was the subject of numerous researches, especially led by German scholars. Known as the Battle of the Column, for decades it has been compromised by a misunderstanding about its location, which must be identified in Columna Reggina - today's Villa San Giovanni - and not Capo Colonna or Punta Stilo as reported by some scholars. This work tries to take the stock of the studies about this subject, and to deepen some tactical aspects of the conflict.
Keywords: Battle of Column; Otto II; Emirate of Sicily; Medieval War; Medieval Calabria; Battaglia della Colonna; Ottone II; Emirato di Sicilia; Guerra Medievale; Calabria Medievale